2009
DOI: 10.4161/cbt.8.12.8561
|View full text |Cite
|
Sign up to set email alerts
|

ERK activation increases nitroprusside induced apoptosis in  human melanoma  cells  irrespective of p53 status: Role of  superoxide dismutases

Abstract: Constitutive ERK activation, superoxide dismutases (SOD) and p53 mutations are implicated in modulating tumor apoptotic response. We now investigated whether human melanoma survival in response to sodium nitroprusside (SNP) is modulated by: (a) stable introduction of a DN-mutant p53; (b) pharmacologically inhibiting ERK activation with UO126; (c) addition of exogenous SOD. Nitroprusside releases nitric oxide (NO) when intact, or acts in a NO-independent manner via iron and residual cyanide after light exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…However, ERK activity has also been involved in activation of the extrinsic pathway by death receptor ligands such as TNF‐related apoptosis‐inducing ligand (TRAIL) [34,42–46], TNFα [47–49], Fas [50,51] or CD40 ligand [52,53]. Cell death induced by other death pathways that occur in response to zinc [54,55], oxidation [56–59], especially in response to ONOO − [60], H 2 O 2 [61–64] or NO treatment [65–67], toxic compounds such as cadmium, [17,68,69], benzo[a]pyrene [70], asbestos [71] or arsenic [17,72], also require ERK activity. Many death stimuli, such as estradiol [73] or its antagonist tamoxifen [74], interferon‐α [75], cephalosporin [76], the calcium mobilizer calcimycin [77], epidermal growth factor (EGF) deprivation [78], leptin [79], bufalin [11], bacterial infection [80,81], chelerythrine [82] and the dominant negative form of Rac and Cdc42 [83,84], are sensitive to inhibition of the Ras/Raf/ERK pathway (Table 1).…”
Section: Ras/raf/erk Pathway Induces Apoptosismentioning
confidence: 99%
“…However, ERK activity has also been involved in activation of the extrinsic pathway by death receptor ligands such as TNF‐related apoptosis‐inducing ligand (TRAIL) [34,42–46], TNFα [47–49], Fas [50,51] or CD40 ligand [52,53]. Cell death induced by other death pathways that occur in response to zinc [54,55], oxidation [56–59], especially in response to ONOO − [60], H 2 O 2 [61–64] or NO treatment [65–67], toxic compounds such as cadmium, [17,68,69], benzo[a]pyrene [70], asbestos [71] or arsenic [17,72], also require ERK activity. Many death stimuli, such as estradiol [73] or its antagonist tamoxifen [74], interferon‐α [75], cephalosporin [76], the calcium mobilizer calcimycin [77], epidermal growth factor (EGF) deprivation [78], leptin [79], bufalin [11], bacterial infection [80,81], chelerythrine [82] and the dominant negative form of Rac and Cdc42 [83,84], are sensitive to inhibition of the Ras/Raf/ERK pathway (Table 1).…”
Section: Ras/raf/erk Pathway Induces Apoptosismentioning
confidence: 99%
“…While it is generally true that melanomas are caused by ultraviolet B induced lesions in melanocytes of the skin, the exact molecular events leading to melanoma production are yet unknown2. Over 90% of melanomas are independent of TP53 gene mutation3, suggesting pathways other than those involved in p53 mediated DNA repair or abrogation of apoptosis by p53 are generally not directly involved. Early events in melanoma induction involve epithelial-mesenchymal transition, and both protein coding and noncoding RNA genes are important4.…”
mentioning
confidence: 99%
“…Western blot data showed that β-lapachone time- and dose-dependently induced pro-apoptotic proteins caspase-3, -8, and -9, PARP cleavage, and increased expression of Bax in B16F10 cells, whereas expression of anti-apoptotic proteins such as Bcl-2 and Bcl-xL was decreased in these cells (Fig 4). MAPKs including p38, ERK, and JNK, are implicated in regulating survival and cell death responses of tumor cells, and play critical roles in the regulation of cell proliferation, differentiation, and apoptosis [21–23]. Thus, we examined whether MAPKs are involved in β-lapachone-induced apoptosis.…”
Section: Resultsmentioning
confidence: 99%